PENGEMBANGAN WAROG SEBAGAI MEDIA PENDIDIKAN KARAKTER CINTA TANAH AIR PADA ANAK USIA DINI - Dian Kristiana; Dian Eka Pratiwi; Betty Yulia Wulansari (Universitas Muhammadiyah Ponorogo, 2017)
The aims of this research is to develop WAROG (Wayang Reyog) as a learning media of love character of homeland in early childhood. This research is a development research. The research location is in TK Surya Kemuning. The collection of data necessary to support the research, observations and interviews instruments. From the interview data then developed WAROG media, then validated, small group trials and product trials. The data obtained from the observations will be analyzed by recording data and describe descriptively. The development of WAROG media uses Sugiono's development model which is limited to product trial steps. WAROG media development the result show to be worthy of use, from the results of testing it can be seen that the application of WAROG media to instill the character of this education with very good criteria.